On the origin of the placename Punià - Palionis, Jonas (Baltistica, 2020)
The name of the small town Punià originates from the apellative Latv. puna, pune “height, eminence”. The said placename serves as a basis for the hydronym Punẽlė.
Keywords: Lithuanian; onomastics; etymology; placename; hydronym; Punia; Punelė